Greece and the Balkans since 1974 - Triantaphyllou, Dimitrios (Études helléniques / Hellenic Studies, 1997)
The author traces the history and development of Greek relations with the Balkans. The article shows how much Greek domestic politics were influenced by the country’s external affairs. The author points out the efforts of Greek politicians and shows the significance of war in the former Yugoslavia and the Macedonian Question.